A Tentative Analysis on the Influential Degree of the Board Characteristics on Firm Performance -- An Empirical Study of China's Listed Companies - WANG, Zhechun (2020)
This study aims to analyze the effect of the characteristics of the board of directors (BOD) of China’s listed companies on the firm performance. Different from previous studies by using multiple linear regression, this research applies panel data for regression analysis and takes into account the time series and cross-sectional correlation. A more constructive empirical study is conducted in this research. By analyzing data of 320 firms listed on the Shenzhen Stock Exchange in the period from 2016 to 2019 and applying fixed effects regression analyses, this empirical research tries to shed light on China's particularities, strengths, and weaknesses in board research and corporate performance. This paper makes a significant contribution to the literature about how corporate governance affects firm performance in developing countries. On the basis of this empirical study, the conclusion suggests that to be successful and improve firm performance, China’s listed companies should resort to a smaller-sized board, more independent board members, and more CEO duality. Moreover, board compensation does not significantly affect firm performance.